CFD Port Flow Simulation of Air Flow Rate in Spark Ignition Engine - SMG Akele; C. Aganama; E. Emeka; Y. Abudu-Mimini; S. Umukoro; Okonkwo Raymond (International Journal of Engineering and Management Research, 2020)
In the early stages of development of internal combustion engine (ICE), limitations such as speed, range, and lifespan led to series of researches resulting in the reduction or elimination of these limitations. Combustion in ICE is a rapid and controlled endothermic reaction between air in oxygen and fuel which is accompanied by significant increase in temperature and pressure with the production of heat, flame and carbon particle deposits. This combustion process is a phenomenon that involves turbulence, loss of air-fuel mixture during inflow and outflow into the cylinder. The objection of this study is to perform port flow analysis on ICE to determine flow rate and swirl at different valve lift under stationary engine parts.Methodology employed to analyze and solve the ICE port flow simulation is the use of CFD software that uses the finite volume method of numerical analysis to solve the continuity, Navier-Stokes and energy equations governing the air medium in the internal combustion engine cylinder. The model geometry for the analysis was generated using the Ansys Design Modeller for one cylinder, one suction port and one exhaust port, and two valves. The domain considered is internal combustion engine suction port with 86741 nodes and 263155 elements. Study results revealed that air mass was more concentrated around the valve and inlet port cross-section with swirling motion seen, air stream experienced turbulence as it flowed downwards inside the cylinder, air stream spread was turbulent which will eventually enhance smooth combustion, swirling air stream moves towards the cylinder wall where it experienced tumbling and turbulent which will eventually enhance smooth combustion. From the simulation it was revealed that mass flow rate of inlet air increases with valve lift.